Preferencia prevista en la Ley del Impuesto a la Renta del uso de comparables domésticos sobre los extranjeros para el análisis de precios de transferencia: ¿conjunto vacío? - Villagra Cayamana, Renée (2019)
Based on the recent works of organizations involved in international taxation, this paper addresses the prevalence the Peruvian Income Tax Law grants to local comparables. For such purpose, the author proposes some potential solutions to face the absence of local comparables in our jurisdiction, and how through them efficient market differences adjustments can be made.